Evaluation of some cellular biomarker proteins, oxidative stress and clinical indices as results of laparoscopic appendectomy for perforated appendicitis in children - Liu, Qiang; Xu, Ke (Cellular and Molecular Biology, 2020)
Laparoscopic appendectomy for perforated appendicitis in children has the advantages of quick recovery, little influence of inflammatory and oxidative stress and low infection rate. Altogether 115 children with perforated appendicitis treated in our hospital from June 2018 to August 2019 were selected and divided into two groups according to different treatment methods. Laparoscopic appendectomy was used as the research group (RG) (67 cases) and open appendectomy (48 cases) as the control group (CG). The clinical indexes (operation time, intraoperative blood loss, ambulation time, incision length, postoperative exhaust time and length of stay) of the two groups were observed. The levels of C- reactive protein (CRP), procalcitonin (PCT), interleukin -6 (IL-6) and tumor necrosis factor-Î± (TNF-Î±) before and after treatment were detected by enzyme-linked immunosorbent assay (ELISA). The levels of oxidative stress factors (superoxide dismutase (SOD), malondialdehyde (MDA)) and the incidence of postoperative incision infection were observed in the two groups. A visual analogue scale (VAS) score was used to evaluate the postoperative pain in children. Logistic regression analysis was used to analyze the risk factors of postoperative incision infection in children. The improvement degree of clinical indicators in RG was significantly better than that in CG. The expression levels of CRP, PCT, IL-6 and TNF-Î± in RG were significantly lower than those in CG. The expression levels of SOD and MDA in RG were significantly better than those in CG. The postoperative incision infection rate in RG was significantly lower than that in CG. The postoperative VAS score in RG was significantly lower than that in CG. Logistic regression analysis results showed that the risk of incision infection was increased in children with operation time over 1h, incision length >3cm, high CRP, high PCT, high IL-6, high TNF-Î±, high SOD and low MDA. Laparoscopic appendectomy for perforated appendicitis in children can effectively reduce intraoperative hemorrhage, postoperative pain, and the damage to the body of children, and can also reduce oxidative stress and inflammatory reaction in children.